Prediction of the Mortality with Comorbidity - Polypharmacy Score in the Osteoporotic Hip Fractures - Camur, S; Celik, H (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2019)
PURPOSE OF THE STUDY Osteoporotic hip fractures commonly associated with comorbid diseases and use of multiple drugs. Polypharmacy status and the comorbidity-polypharmacy score (CPS) are the most common two grading system to predict mortality risk for the trauma patients older than 45 years. The purpose of the study was to determine whether the CPS or polypharmacy can predict the mortality risk in the older patients had a surgery due to an osteoporotic hip fracture. MATERIAL AND METHODS Consecutive patients aged > 65 years had an osteoporotic hip fracture due to a simple trauma were enrolled in the study. Detailed data were collected included comorbid conditions, medications, T-scores and additional fractures. Patients were divided into four groups according to CPS classification and polypharmacy status was indicated in case of using five or more drugs before admission. Overall mortality was assessed using Kaplan-Meier survival testing. Factors influencing 1-year, 2-year and 5-year mortality were evaluated using a multivariate logistic regression model with adjusted odds ratios (AORs) and a threshold significance at p < 0.05. RESULTS A total of 109 patients (65% women) with a mean age 80 ± 8.06 were included in the study. The mean time to death from the surgery was 42.06 ± 34.9 months. The Kaplan-Meier survival curves showed a significant difference in mortality among CPS groups. (Log-Rank test < 0.001). CPS presented a significant prediction in 1-year (AOR: 4.2; p < 0.05) and 2-year mortality (AOR: 2.9; p < 0.05) after adjustment for several covariates (including age, gender, surgical procedure) whereas 5-year mortality did not reveal a significant prediction (p = 0.46) Polypharmacy existence did not independently predict both overall or year-based mortality (p > 0.05) . CONCLUSIONS CPS is a better predictor for mortality risk than polypharmacy existence in the first two years in the patients underwent surgery for an osteoporotic hip fracture. Key words:osteoporotic hip fracture, mortality, polypharmacy, comorbidity.
Keywords: Comorbidity; Male; Risk Factors; ukazatele zdravotního stavu; Polypharmacy; Aged; mužské pohlaví; senioři; Hip Fractures; komorbidita; senioři nad 80 let; lidé; ženské pohlaví; Humans; polypharmacy; rizikové faktory; Aged, 80 and over; osteoporotické fraktury; Female; Health Status Indicators; fraktury kyčle; Osteoporotic Fractures